2019
DOI: 10.1186/s13071-019-3517-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface sterilization methods impact measures of internal microbial diversity in ticks

Abstract: Background Ticks are obligate blood feeders transmitting major pathogens worldwide. Over the past few years, considerable research efforts have focused on the diversity, distribution and impact of gut and intracellular bacterial symbionts on tick development and tick-borne pathogen transmission. The study of this internal microbiome requires the use of a sterilization method to remove external (i.e. cuticular) microbes present on the tick’s surface and to avoid any further contamination. Several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 72 publications
3
79
0
Order By: Relevance
“…Probably both. Indeed, Binetruy et al [66], demonstrated that the tick surface sterilization using ethanol (as we did in the present study) did not efficiently remove bacterial DNA from the tick cuticle compared to bleach. They also showed that environmental taxa, only detected in ethanol cleaned entire ticks, belonged to the same family than those directly detected on the tick cuticle by swabbing.…”
Section: • Ixodes Ricinus Microbiota Diversity and Compositionmentioning
confidence: 41%
“…Probably both. Indeed, Binetruy et al [66], demonstrated that the tick surface sterilization using ethanol (as we did in the present study) did not efficiently remove bacterial DNA from the tick cuticle compared to bleach. They also showed that environmental taxa, only detected in ethanol cleaned entire ticks, belonged to the same family than those directly detected on the tick cuticle by swabbing.…”
Section: • Ixodes Ricinus Microbiota Diversity and Compositionmentioning
confidence: 41%
“…Particular attention should be payed to the washing and surface sterilization steps prior to the extraction to avoid as much as possible external contaminants. Even though the effect of surface microbes in the whole microbiome assessment may be minimal as well (Hammer et al, 2015), the method used for surface sterilization can impact the microbiome diversity retrieved (Binetruy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Tokarz et al disputed the identification of Bartonella as a component of the I. scapularis microbiome, attributing the mistake to a lack of specificity in primer design (Tokarz et al, 2019). Another factor that can inflate bacterial diversity estimates is the method of tick sterilization employed prior to sequencing, where ethanol-based surface sterilization of Amblyomma cajennense ticks correlated with reports of higher internal bacterial diversity than studies that used bleach-based methods, likely due to cuticular contaminants that were not removed by ethanol (Binetruy et al, 2019). Finally, detection of microbial DNA does not in and of itself prove that a specific species is a component of the microbiome.…”
Section: Microbiota Of I Scapularismentioning
confidence: 99%